No intention to comply with pneumococcal vaccination: in the elderly - Collar, Kristin M. (My University, 2011)
The purpose of this study was to explore and describe the experience of refusing the pneumococcal vaccine from the perspective of adults 65 years and older. Pneumococcal disease is a leading cause of serious illness in adults, particularly those 65 years of age and older. Despite numerous studies on barriers and facilitators to pneumococcal vaccination, little research has focused solely on those patients who refuse vaccination.To enhance the healthcare provider's understanding, the following research question was asked: What are the factors that influence adults, 65 years and older, when making a decision to not receive the pneumococcal vaccine? The Health Belief Model (HBM) provided the framework for this research. A phenomenological qualitative design was used to gather narrative data in order to explore and describe their experiences. The sample was obtained through purposive convenience samples of participants who have refused a pneumococcal vaccination within the last year. The setting for data collection was determined by the participants for their convenience (home, etc.). A demographic questionnaire was utilized to aid in data collection, and semi-structured face-to-face interviews were conducted using openended questions. The researcher was the instrument for data collection. Interviews were audio-taped and transcribed verbatim. Data were analyzed utilizing Colaizzi's (1978) approach.
A Clinical Paper submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing-Family Nurse Practitioner
Keywords: Medicine - Preventive; Pneumococcal vaccine; Pneumonia, Pneumococcal - vaccination; Immunization of older people; Vaccination